The Problem of Waqf Land Legality in Sarmi Regency: A Sociological Perspective of Law - Ilyas, Muhammad; Huda, Mifathul; Faisal, Faisal (Al-Bayyinah, 2023)
The problem of legality and management of waqf land in the midst of Muslim community life in the realm of praxis, often triggers case problems, such as the withdrawal of the waqf land, the seizure of waqf land and others. This study intends to identify factors of ineffective regulation on waqf land certification in Sarmi District, Papua Province. This qualitative study is empirical legal research. SoerjonoSoekanto's theory of legal effectiveness became the theory of subject matter analysis. Data collection through observation techniques, interviews and documentation. Meanwhile, data analysis uses data reduction, presentation, and verification techniques. The results of this study show that the ineffectiveness of regulations related to certification of various waqf lands in Sarmi Regency is caused by the views of the community which is a weak legal culture, including the view that there will be no waqf land disputes, the view of the difficulty of the waqf land certification process, the view of the Wakf Pledge Deed as the legality of waqf land. The theoretical implications and novelty of this study emphasize that to realize the effectiveness of the implementation of waqf land certification, massive and comprehensive socialization is needed related to understanding of the waqf land certification program and waqf land management management. The limitation of this study is that it has not examined the role of Islamic religious leaders in Sarmi Regency regarding the waqf land certification program.